STUNNING ON ANIMALS SLAUGHTER ON ISLAMIC LAW PERSPECTIVE - Ahmad Yani; Rudi Ahmad Suryadi; Nurrohman nurrohman (IAIN Manado, 2020)
The research aimed to analyze the study of Islamic law regarding slaughter and stunning, and provide an assessment of the benefits of the slaughter and slaughter results. The research method is a library study in which the process is by collecting book data and other reading sources. Data sources in the form of fiqh references and ICU fatwas, accompanied by empirical research findings on stunning. The main references are obtained from al-Fiqh al-Islami wa Adillatuhu, al-Haram wa al-Haram, Kasysyaf al-Qina’, and several books of hadith and fiqh. The research found that stunning is permissible by paying attention to temporary fainting animals, does not cause death and permanent injury, aims to facilitate slaughter, and not to torture animals. Slaughter by conventional means is recommended. The benefit is based on the indicator that animals die faster. Opinions of Ulama and ICU Fatwa encourage the slaughter manually without stunning.